Edukasi Stimulasi Deteksi Tumbuh Kembang Bayi, Anak dan Pra Sekolah di Desa Bangun Rejo Kecamatan Tanung Morawa Kabupaten Deli Serdang - Damayanty S; Martha Armita Silaban; Amelia Erawaty Siregar; Ade rachmat yuliyanto; Ingka Kristina Pangaribuan; Dina Afriani (Pusat Riset dan Inovasi Nasional, 2022)
SDIDTK activities are not only carried out for children who are suspected of having problems, but must be carried out for all pre-schools and pre-school children on a regular basis twice a year. So from within this community service program early detection of the growth and development of preschool children at PAUD/TK Ar-Raafi Medan Methode : Checking growth and development in infants and toddlers is by checking their weight and height. Developmental tests using KPSP infants and toddlers. Results : Participants in this activity were infants and preschoolers in Sumber Rejo village, totaling 81 children. After counseling and examination of children's growth and development using the KPSP and measurements of weight and height, there were several children who experienced deviations in growth and development. Conclusion : carried out community service activities based on infant, child and pre-school health in the village of Bangun Rejo, Tanjung Merawa sub-district, Deli Serdang district. The service activity was carried out for 3 months. The results of this Community Service regarding early detection of child growth and development. This community service has been carried out from August to September 2022 to be precise for 3 months